The methionine aminopeptidase 2 inhibitor ZGN‐1061 improves glucose control and weight in overweight and obese individuals with type 2 diabetes: A randomized, placebo‐controlled trial. Issue 7 (3rd March 2020) - Wentworth, John M.; Colman, Peter G.
Abstract: The methionine aminopeptidase 2 (MetAP2) inhibitor ZGN‐1061 lowered weight and improved glucose in preclinical studies. We sought to determine its efficacy and safety by performing a multicentre, phase 2, randomized controlled trial involving overweight and obese adults with type 2 diabetes and HbA1c between 7% and 11% inclusive. Participants were randomized to receive subcutaneous treatment with placebo or 0.05, 0.3, 0.9 or 1.8 mg ZGN‐1061 every third day for 12 weeks. The primary outcome was change in HbA1c at week 12. Relative to placebo, the 0.9 and 1.8 mg doses induced clinically meaningful reductions in HbA1c of 0.6% (95% CI 0.2% to 0.9%; P = 0.0006) and 1.0% (95% CI 0.6% to 1.4%; P < 0.0001), respectively. The 1.8 mg dose also induced weight loss of 2.2% (95% CI 1.1% to 3.3%; P = 0.0002). The incidence of adverse events was balanced across the treatment groups. We conclude that MetAP2 inhibition with ZGN‐1061 for 12 weeks improved glucose control and aided weight loss in overweight and obese people with type 2 diabetes. However, given safety issues, Zafgen has discontinued MetAP2 inhibitor development.